2008
DOI: 10.1016/j.juro.2007.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Initial Extended Transrectal Prostate Biopsy—Are More Prostate Cancers Detected With 18 Cores Than With 12 Cores?

Abstract: Compared with 12-core prostate biopsy, 18-core prostate biopsy detects significantly more cases of high grade prostatic intraepithelial neoplasia. However, 18-core prostate biopsy detects a significantly higher number of cancer only in patients with a prostate volume of 55 cc or greater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 20 publications
1
32
1
9
Order By: Relevance
“…[4][5][6] Additionally, we found PCa in 41.5% of the patients which is compatible with the literature. [14][15][16][17] However, TCL and ACL were not significantly associated with PCa in our multivariate analysis. Furthermore, when we pooled all cores, we found no significant difference among cores regarding MCL.…”
Section: Discussioncontrasting
confidence: 51%
“…[4][5][6] Additionally, we found PCa in 41.5% of the patients which is compatible with the literature. [14][15][16][17] However, TCL and ACL were not significantly associated with PCa in our multivariate analysis. Furthermore, when we pooled all cores, we found no significant difference among cores regarding MCL.…”
Section: Discussioncontrasting
confidence: 51%
“…Alternatively, several groups have noted the need for more biopsy cores from larger glands. [24][25][26] Scattoni et al…”
Section: Discussionmentioning
confidence: 99%
“…[24] first examined 13 cores; they found that this particular scheme resulted in a 35% increase in the PCa detection rate. Similarly, Scattoni et al [25] assessed the diagnostic yield of a scheme using 18 cores in 1776 patients and compared it with the 12-core biopsy strategy. No statistically significant difference in the PCa detection rate was observed between the 2 strategies except in patients with a prostate volume of less than 55 cc (+6.7% gain was recorded).…”
Section: Extended Biopsy Schemementioning
confidence: 99%
“…No statistically significant difference in the PCa detection rate was observed between the 2 strategies except in patients with a prostate volume of less than 55 cc (+6.7% gain was recorded). [25] It is clear that the yield of sextant biopsy can be significantly improved when extended biopsy is performed. However, as the number of cores exceeds 10, the gain becomes more marginal.…”
mentioning
confidence: 99%